Examining the Effects of Internal Communication and Emotional Culture on Employees' Organizational Identification. (April 2021) - Yue, Cen April; Men, Linjuan Rita; Ferguson, Mary Ann
As one of the first empirical attempts investigating the emerging role of positive emotional culture within organizations, the study examined how a symmetrical internal communication system and leaders' use of motivating language contribute to fostering a positive emotional culture featured by joy, companionate love, pride, and gratitude. Furthermore, the study examined the linkage between a positive emotional culture and employees' organizational identification. A quantitative online survey was conducted with 482 full-time employees in the United States. Results showed that both symmetrical internal communication and leaders' use of motivating language, including meaning making, empathetic, and direction-giving languages, induced employees' perception of a positive emotional culture of joy, companionate love, pride, and gratitude, which in turn enhanced employees' organizational identification. Positive emotional culture fully mediated the impact of corporate and leadership communications on employee identification with the organization. Theoretical and practical implications of the findings are discussed.